Molecular characterization of colistin resistant Escherichia coli in live chickens, raw chicken meat and fresh vegetables in Kelantan, Malaysia - Susmita Seenu Devan (2023)
The uncontrolled usage of colistin as a growth promoter in poultry and the poultry manures utilized as fertilizers in vegetable crop farming are the fundamental causes of mobilized colistin resistance (mcr) gene emergence, especially in Escherichia coli (E. coli). Thus, this study was conducted to determine the prevalence, antibiotic susceptibility profile and molecular characterization of colistin resistant E. coli isolated from poultry farm (chicken cloacal swab, raw chicken meat, and vegetables from markets in Kelantan,Malaysia. Based on the samples collected (vegetables = 100; chicken meat = 200; cloacal swab = 217), the genotypic prevalence of E. coli was 71.0% (367/517). About 5.4% (20/367) isolates harboured mcr-1, mcr-3, mcr-6, mcr-8 and mcr-9 genes from chicken origin alone, while no mcr was detected in vegetables. The E. coli isolates were tested with disk diffusion antibiotic and colistin susceptibility tests. The findings revealed that; 96.1%, 100.0% E. coli isolates from chicken meat and clocal swabs were resistant towards tetracycline followed by ampicillin, amoxicillin, and chloramphenicol. Almost all chicken origin isolates showed MAR index of more than 0.2 and ten mcr- harbouring isolates showed MIC ≥ 4 ug/ml. In contrast, almost all vegetable E. coli isolates were still sensitive towards those antibiotics. Furthermore, 45.1% and 20.0% isolates from chicken belonged to phylogroup A and B1 respectively. Whereas 59.4% isolates from vegetable belonged to phylogroup A. In addition, virulence genes astA, papC, iss and iucD were detected from the chicken origin colistin resistant E. coli isolates. The clonal expansion of the 14 mcr-carrying E. coli was further analysed with multi-locus sequence typing (MLST) and 13 sequence types (STs) were identified; ST10, ST38, ST354 and ST155 were among them. The findings underscore the emerging threat of multidrug resistance and increasing trends of mcr gene in E. coli, in food animals in Malaysia. Therefore, further studies need to be conducted on the molecular epidemiological information of these isolates for better understanding of the identified colistin resistant isolates, that can contribute to the national antimicrobial resistance (AMR) control in future.